PENGARUH PEMAHAMAN KODE ETIK, NILAI ETIS, PRINSIP MORAL DAN KOMPENSASI TERHADAP PERILAKU ETIS (Studi Pada Kantor Akuntan Publik di Kota Malang) - Muhamad Yasin La Buda; Abdul Wahid Mahsuni; Afifudin Afifudin (Universitas Islam Malang, 2020)
The research aims to determine the effect of understanding the code of ethics, ethical values, moral principles and compensation on ethical behavior. The population of this research is the Public Accounting Firm (KAP) located in Malang. Sampling uses the Purposive Sampling method and there are 6 Public Accounting Firms (KAP) that fit the criteria. This study uses multiple linear regression models. In this study shows that understanding the code of ethics has a positive effect on ethical behavior. Ethical value has a positive effect on ethical behavior. Moral principles do not affect ethical behavior. Compensation has no effect on ethical behavior. Keywords : Understanding of the code of ethics, ethical values, moral principles, compensation, ethical behavior.